Economic crisis slows European convergence - Matthias Diermeier; Markos Jung; Pekka Sagner (Institut der deutschen Wirtschaft (IW), 2018)
Up until the economic and financial crisis, economic conditions in the European regions had been converging. This process has come to a complete standstill in recent years due to lower growth in Eastern Europe and stagnation in Southern Europe.
Keywords: 330